Penerapan Hukum Pidana Pada Korporasi yang Melakukan Tindak Pidana Perpajakan - Glenn Merciano Eben Rohi; I Nyoman Gede Sugiartha; Ni Made Puspasutari Ujianti (Fakultas Hukum Universitas Warmadewa, 2022)
The implementation of national development as a major project certainly requires not only the active participation of the entire nation, but also requires significant costs. The costs incurred to carry out development are not only borne by the state. Relying on aid or grants from abroad will cause the burden of economic dependence which has an impact that foreign countries with stronger economic powers will dictate the life of the Indonesian nation. Realizing this, one of the dominant sectors as a source of state revenue is the tax sector. In Articles 38 to 39A of the KUP Law, none of these articles include sanctions for corporations, although corporations can act as taxpayers, none of these articles explicitly states who is responsible for criminal violations in the tax and tax sector. what form of crime is appropriate to be imposed on corporations that commit tax crimes. Criminal law in an effort to overcome crime in the field of taxation is to create integration in the criminal law policies that are applied, the impact of which will not make it difficult for law enforcement officers to apply them in tax legislation. The imperative element contained in the taxation legislation, would like to include a principle that the use of criminal sanctions should still pay attention to the principle of subsidiarity.